2022
DOI: 10.1186/s12882-022-02881-w
|View full text |Cite
|
Sign up to set email alerts
|

What happens after the kidney biopsy? The findings nephrologists should know

Abstract: Background Percutaneous kidney biopsies are important tools for the diagnosis of kidney diseases. Nephrologists must be familiar with the expected complications of the procedure to provide an adequate informed consent. Here, we present a quality improvement analysis that reviews the complication rate of percutaneous kidney biopsies performed over a 2-year period by nephrologists at a single center, and that tabulates the nature and timing of these events. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…15 Recognizing the possibility of pain and anxiety with a kidney biopsy is an important part of participant education and preparation for the KPMP study procedure. 13 Comfort measures and support are provided according to the study site's standards of care. Interestingly, playing music during moments of distress with comparably uncomfortable procedures, for example, shock wave lithotripsy for kidney stones or hemodialysis, may provide relief and improve the overall experience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Recognizing the possibility of pain and anxiety with a kidney biopsy is an important part of participant education and preparation for the KPMP study procedure. 13 Comfort measures and support are provided according to the study site's standards of care. Interestingly, playing music during moments of distress with comparably uncomfortable procedures, for example, shock wave lithotripsy for kidney stones or hemodialysis, may provide relief and improve the overall experience.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported similar findings after clinically performed kidney biopsies. 13,14 However, surveys are not standardized pain assessments. Nevertheless, our survey data provide reassurance that kidney biopsies are generally well tolerated in KPMP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In einer Studie mit 750 Patienten nach einer PNB wurden 2 Drittel der relevanten Komplikationen innerhalb von 8 Stunden bzw. 1,3 % (n = 2) der Komplikationen bei 154 Biopsien nach 4 Stunden detektiert 21 , 22 .…”
Section: Nachbeobachtungunclassified